Numerical and Experimental Studies on the Cutting Energy Requirements of Okra (Abelmoschus esculentus L.) - Asonye, U. G.; Nwakuba, N. R.; Asoegwu, S. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Cutting energy requirements for vegetable crops is a prerequisite in the engineering design of appropriate cost effective cutting systems consuming minimum amount of energy while still providing high quality products. This study attempts the development of predictive equations describing the cutting energy for okra (Abelmoschus esculentus L.). Dimensional analysis based on the Buckingham pi theorem was used to obtain the functional relationship between the cutting energy of the selected vegetable and the independent variables such as tool weight (w), height of tool drop (Hd), tool edge thickness (t), cutting speed (v), crop size (s), crop moisture content (φ), crop contact area (A) and crop density (σ). The developed model was validated with experimental data. A high coefficient of determination of R2 value of 0.973 between the predicted and measured energy values showed that the method is good. Hence the obtained predictive model is appropriate for determining the cutting energy requirements of okra up to 97%.